Challenges faced by tax compliant microenterprises in Midrand - Letsoalo, Simon (My University, 2014)
Microenterprises have the potential to address the triple challenges of unemployment, poverty and inequality because of the opportunities they present to the socially and economically disadvantaged in South Africa. This has a spillover effect of growing the economy. However, the challenges faced by tax compliant microenterprises as uncovered in this qualitative research, limits them in meeting potential. Twelve respondents comprising of three clusters (tax practitioners, microenterprise owners and SARS official) were purposefully and conveniently sampled to give their views and opinions about the challenges. The lack of expertise, SARS' evolving rules and regulations, financial costs of being compliant, onerous tax compliance preparations, and constitutional ambiguity and unclear definition of microenterprises were observed to be the major challenges that tax compliant microenterprises face. Although the South African government is not oblivious of the dilemma that tax compliant microenterprises often find themselves in, more needs to be done to ease their plight in operating in an enabling business environment. This study provides an insight into the current and future tax issues that government needs to address towards creating an enabling tax environment for businesses. The scope of this paper is limited as the researcher sought to bring to light the challenges faced by microenterprises. Other emerging issues, such as the benefits of being compliant could not be fully established and paves the way for further research.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2014.
Keywords: Tax compliance; Microenterprises; Challenges in tax compliance